HER2 gene amplification in patients with breast cancer with equivocal IHC results - Meijer, Sybren L; Wesseling, Jelle; Smit, Vincent T; Nederlof, Petra M; Hooijer, Gerrit K J; Ruijter, Henrique; Arends, Jan Willem; Kliffen, Mike; van Gorp, Joost M; Sterk, Lotus; van de Vijver, Marc J (Journal of clinical pathology, 2011)
AimsEquivocal human epidermal growth factor receptor 2 protein (HER2) (2+) immunohistochemistry (IHC) is subject to significant interobserver variation and poses a challenge in obtaining a definitive positive or negative test result. This equivocal test result group accounts for approximately 15% of all tumours, and for optimal guidance of HER2 targeted therapy, a further analysis of quantification of gene copy number and amplification status is needed for patients with early or metastatic breast cancer.Methods553 breast-cancer specimens with equivocal HER2 IHC(2+) test results were collected and subsequently centrally retested by chromogenic in situ hybridisation (CISH), and HER2 gene copy numbers per tumour cell nucleus were determined.ResultsUsing CISH, 77 of 553 equivocal HER2 IHC(2+) test result cases (13.9% of total) showed high levels of HER2 gene amplification (≥10.0 gene copies per nucleus), and 41 of 553 (7.4% of total) showed low-level HER2 gene amplification (6.0–9.9 gene copies per nucleus). In 73.6% of cases, no amplification of the HER2 gene was shown, and in only 4.9% of cases was an equivocal test result by CISH observed (4.0–5.9 gene copies per nucleus).ConclusionsTesting by CISH of all equivocal HER2 IHC(2+) test result provides a definitive guidance in HER2 targeted therapy in 95.1% of cases. A significant proportion (21.3%) of patients with equivocal IHC(2+) test results show amplification of the HER2 gene.